A study of acute respiratory disease in the community of Port Chalmers. II. Influenza A/Port Chalmers/1/73: intrafamilial spread and the effect of antibodies to the surface antigens. - Jennings, L. C. (Cambridge University Press, 1978)
During the first year of a study of respiratory disease in the semi-isolated community of Port Chalmers, New Zealand, an epidemic of clinical influenza occurred from which the variant influenza A/Port Chalmers/1/73 (H3N2) was isolated. Within a selected group of 26 families, 59 (46%) members had clinical or laboratory evidence of infection. During intrafamilial spread the infection frequency was highest for school-aged children (77%), followed by female adults (67%), infants (64%) and male adults (41%). The index infection in each family was a school-age child on 10 occasions, suggesting the role of this age group in the transmission of influenza A in this community. The secondary attack rate (SAR) of 58.3% was higher than expected. In sera taken before the 1973 epidemic, 59% of family members had detectable HI antibody and 25% NI antibody to A/England/42/72 while 38% had detectable HI antibody and 8% NI antibody to A/Port Chalmers/1/73. The relation between pre-existing antibody and infection frequency is discussed.